Genetic Fingerprinting of Pseudomonas aeruginosa Involved in Nosocomial Infection as Revealed by RAPD-PCR Markers - Akanji, B.O.; Ajele, J.O.; Onasanya, A.; Oyelakin, O. (Science Alert, 2010)
Genetic fingerprinting of 30 Pseudomonas aeruginosa (Pa) isolates from three types of nosocomial infection cases from two Osun State Teaching Hospitals was compared using RAPD-PCR markers. Ten out of 50 operon primers tested showed polymorphism with reproducible results among the isolates and produced 131 bands of which 74 were polymorphic with sizes ranging between 200 and 3,000 bp. Cluster analysis using the 74 polymorphic markers classified the 30 Pseudomonas aeruginosa isolates into two (PgA and PgB) genetic groups. Comparing isolates proportion in each genotype based on their site of infection, antibiotics resistance pattern and geographical location, it was revealed that the proportion of urinary tract infection isolates in PgA genotype was significantly less than those in PgB genotype (z = -1.195, p<0.05) while the proportion of septicaemia isolates in PgA genotype was significantly higher than its proportion in PgB genotype (z = 1.348, p<0.05). However the proportion of wound infection isolates of PgA and PgB genotypes were significantly the same (z = -0.278, p>0.05). The PgA genotype contained few isolates with increased virulence and resistance to new antimicrobial modules and could possibly be new emerging P. aeruginosa strains from PgB genotype population. The study has critically revealed the genetic diversity and distribution among P. aeruginosa isolates in Osun State